Analysis of the Validity of the Instrument for Early Childhood Numeracy Literacy Assessment - Yudha, Rivo Panji; Hetharia, Teguh Samudra (Kirana Publisher (KNPub), 2025)
Numeracy literacy in early childhood is a fundamental aspect of cognitive development; however, valid assessment instruments remain limited in Indonesia. This research aims to analyze the validity of numeracy literacy assessment instruments for early childhood in Cakranegara District, Mataram, Lombok. Employing a descriptive quantitative approach, the study involved 135 children with data collection methods through direct observation and numeracy tests. Instrument validation was conducted through content validity testing by three early childhood education experts and exploratory factor analysis (EFA) using Principal Component Analysis method. The research results indicate that the prototype instrument achieved an average validation score of 87.11%, with a Kaiser-Meyer-Olkin (KMO) value of 0.725 and a significant Bartlett's test (χ2 = 968.515; p < 0.000). The inter-rater reliability test yielded an average value of 0.85, falling into the high category. This research produces valid, reliable, and contextual numeracy literacy assessment instruments that can be used to identify the numeracy development of early childhood children more accurately and effectively.